Cryptanalysis of the Vesta-2M stream cipher - GUAN Jie (Tongxin xuebao)
The security of stream cipher Vesta-2M used in commercial products in Russia is analyzed. The size of the initial key of the keystream generator of stream cipher Vesta-2M is)2（536O. The author point out the mistake of attack introduced by the paper [1], and introduce a known plaintext attack method where only a small segment of known plaintext（about hundreds of bits） , the upper bound of the compute complexity is）2(372O.